River cruise impact towards local community : an exploratory factor analysis approach / Faieznor Mohd Nasir and Mohd Hafiz Hanafiah - Mohd Nasir, Faieznor; Hanafiah, Mohd Hafiz (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
The demand for cruising has increasingly grown over the years which create a new trend for tourist to seek for a vacation in a different environment. The rapid growth of river cruise and geographical expanding has increased the cruising complexity and growing the socio-economic, environmental and cultural impacts. Therefore, the consequences of river cruise development should be assessed on how it affects primarily to the community in a tourism destination. In this study, the community perception towards the impacts of river cruise tourism development was assessed through a survey, emphasizing on four key elements: the economic, environmental, cultural and social implications. Exploratory Factor Analysis (EFA) was employed to identify the underlying structure or dimensions in the independent variables in this study. The EFA test confirmed that the tourism development impact dimension consists of four aspects; economic, environment, social impacts and cultural impacts. The result of the EFA also confirms that not all well-developed research items are generic and suitable for different research scope and setting.